Conversations about the History of Ideas - Burton, Howard (Ideas Roadshow Collections., 2020)
Conversations About The History Of Ideas is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading intellectual historians with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Stefan Collini, Professor Emeritus of Intellectual History and English Literature at the University of Cambridge;2. Darrin McMahon, the Mary Brinsmead Whe.